Research on Type Selection of Truss Bridge Structure Based on Optimization Design - Zhang, Bowen (Transactions on Engineering and Technology Research, 2024)
Truss selection design is an important link in both theoretical research and practical engineering problems. The topic of this study is truss selection based on optimization design. Firstly, this paper analyzes the mechanical properties. Then, the material ratios of the three different truss structures are studied by changing the axial force data of the three members using the structural mechanics solver. Finally, through comprehensive analysis and system optimization consideration, the conclusion is drawn that the parallel truss has better performance than the triangular truss and the parabolic-like truss. Through the comparison of three common truss structures and the comprehensive consideration of force analysis, the different advantages and disadvantages of the three trusses are obtained, which provides reference for the selection design of trusses. This paper aims to provide an effective reference for the optimization design of trusses, and also provides inspiration for other professionals to study more types of trusses in the future.